Violence against women: effective interventions and practices with perpetrators : a literature review - Brooks-Hay, Oona (Report, 2014)
The key focus of the report is on reviewing evidence about reducing re-offending in crimes of violence against women. The research evidence available provides a number of valuable insights into what works to reduce reoffending in the area of violence against women.